Debating humanity : towards a philosophical sociology - Chernilo, Daniel (Cambridge : Cambridge University Press, 2017)
Debating Humanity explores sociological and philosophical efforts to delineate key features of humanity that identify us as members of the human species. After challenging the normative contradictions of contemporary posthumanism, this book goes back to the foundational debate on humanism between Jean-Paul Sartre and Martin Heidegger in the 1940s and then re-assesses the implicit and explicit anthropological arguments put forward by seven leading postwar theorists: self-transcendence (Hannah Arendt), adaptation (Talcott Parsons), responsibility (Hans Jonas), language (Jürgen Habermas), strong evaluations (Charles Taylor), reflexivity (Margaret Archer) and reproduction of life (Luc Boltanski). Genuinely interdisciplinary and boldly argued, Daniel Chernilo has crafted a novel philosophical sociology that defends a universalistic principle of humanity as vital to any adequate understanding of social life.
Title from publisher's bibliographic system (viewed on 19 Jun 2019).
Open Access title.
Keywords: Humanism; Human beings; Philosophical anthropology